Retrieving local effective constitutive parameters for anisotropic photonic crystals - C. Tserkezis; N. Stefanou (Physical Review B, 2010)
We propose a method for calculating average local effective permittivity and permeability tensors for anisotropic photonic crystals through least-squares fits of sets of data points, obtained by rigorous, systematic complex-band-structure, and reflection calculations for all propagation directions, to appropriate analytic expressions. The proposed methodology is applied on a specific example of a tetragonal structure of metallic nanoshells, which is a uniaxial photonic crystal of resonant units. Our results demonstrate the efficiency of the method at low and moderate frequencies and, at the same time, reveal the inability to define local effective constitutive parameters in regions of resonance gaps.